Paediatric appendicitis scoring: a useful guide to diagnose acute appendicitis in children - Dhruv, Kamlesh Kumar; Singh, Krishna Kumar; R., Patley D.; S., Painkara U. (International Surgery Journal, 2016)
Background: Pain in abdomen is common reason for which a child is brought to a surgeon and acute appendicitis is one of the common differential diagnoses in these children. In spite of availability of modern radiological and pathological investigations, even today the diagnosis of acute appendicitis depends mainly on clinical grounds and simple blood count. Pediatrics appendicitis scoring (PAS) which is based on clinical symptoms and sign along with WBC count is a good guide in diagnosis of acute appendicitis. The patient with scoring more than 7, were found to have acute appendicitis and required surgical intervention while those with score <5 could be treated conservatively without any squeal. The Paediatric appendicitis scoring could be helpful to diagnose acute appendicitis early thus reducing morbidity and mortality of the condition by early surgical intervention on one hand and reducing unnecessary exploration on the other. Methods: Patients of acute abdomen admitted in paediatric surgical ward of Kamla Nehru Hospital, Gandhi Medical College, Bhopal, MP, India during the period 14 October 2002 to 03 October 2003 were studied. All the case (25) of acute abdomen suspected to be acute appendicitis were included in this series. A uniform prospective data form was completed which included Demographic data, duration of symptoms, Physical signs, Laboratory, Histopathological examination. Patients were classified into two groups, group I with appendicitis and group 2 nonappendicitis according to final score obtained by each variable. Patients with scoring >7 were included in group I while those with >5 scoring were in group 2. Treatment was given accordingly. (Operative or Non-operative) outcome of the study was noted. Results: In the study, children of age group from 4 to 12 years were included; peak incidence was between 8-10 years, with male: female ratio of 3:1. The size of incidence in both the sex is maximum between 9 to 12 years of age. Tenderness in the rt. Lower quadrant of abdomen on cough/percussion/hopping and tenderness over right iliac fossa has the highest incidence. Leucocytes also has the sensitivity of >75% while anorexia is least sensitive. The patients were grouped in two categories as per the paediatric appendicitis scoring, those patients with PAS >7 were grouped under group I, 10 out of 15 patients underwent appendectomy. Conclusions: Pediatric appendicitis score is a simple relatively accurate diagnostic tool for accessing an acute abdomen and diagnosing acute appendicitis in children. According to this study, PAS is of value in the preclinical evaluation of patients with suspected acute appendicitis and may be instrumental as a quality control tool and in clinical guidelines.